ANALISIS BIAYA ANTIBIOTIKA DAN BIAYA PERAWATAN FRAKTUR TULANG DALAM PENETAPAN PEMBIAYAAN KESEHATAN BERDASARKAN INA- CBG’S DI RSUD ULIN BANJARMASIN - Amaliyah Wahyuni; Mochammad Maulidie Alfiannor Saputera (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
The government implements a universal health insurance system for all Indonesian citizens, called the BPJS (National Health Insurance Provider). In the BPJS service there is a fixed financing package system based on INA-CBG's. The INA-CBG package for bone fractures requires planning. With the INA-CBG package rates, it is expected to be able to reduce the high health costs including the cost of treatment for the fracture. The purpose of this study was to determine the magnitude of the percentage of the total cost of using antibiotics and plates of the total cost of treating bone fracture patients in real accordance with the INA-CBG rates at Ulin Hospital Banjarmasin. This research was an observational study which presented quantitative descriptive data with retrospective data collection. The study sample used BPJS patients with the main diagnosis of bone fractures according to data from the medical records during the period January - December 2018 at Ulin Hospital Banjarmasin in accordance with the criteria. The average value of bone fracture treatment costs by class are class III: Rp. 16,317,084, class II: Rp. 15,119,497, class I: Rp. 17,983,348, and according to severity, namely severity level I: Rp.14.825.222, severity level II: Rp. 29.409,525, severity level III: Rp.26,997,643. There is a mismatch / difference between the real treatment costs and the INA-CBG package rates for bone fracture patients. And the percentage of the total cost of using antibiotics is 0.9% and 45.92% of the total real cost of treating bone fracture patients at Ulin Hospital Banjarmasin